Amway as Neoliberal Religious Tradition - Laminack, Michael (Religions, 2021)
Why do people desire their own continued oppression under neoliberalism? This essay seeks an answer to this confounding question through analysis of the Amway organization, an American multi-level-marketing (MLM) company that rose to a multi-billion dollar value in the 1980s and 90s. My argument is that Amway serves as a prime case study for the relation between neoliberalism and religious practices--people desire their continued oppression under neoliberalism in part because neoliberalism bears meaning at the level of culture and religion. What sets Amway apart from other MLMs, and makes Amway a prime case study for neoliberalism and religious practices, is its amalgamation of neoliberal ideology with ideas and trends from American evangelicalism, to the extent that it serves as a kind of neoliberal religious tradition. As this amalgamation demonstrates, people may defend neoliberalism with a similar fervor as defending cultural or religious traditions. The conclusion explores the possibility of a decolonial American evangelicalism, which would seek options for broadening the horizons of American evangelicalism beyond the relationship to neoliberalism and the possibility of a critical theology robust enough to thoughtfully critique neoliberalism. In pursuit of this thesis, the essay utilizes a theoretical framework guided by the contributions of scholars including Wendy Brown, Walter Benjamin, Olivier Roy, Walter Mignolo, and Carl Raschke in order to analyze Amway through the lens of contemporary political theories of neoliberalism.